2019
DOI: 10.1111/jocn.14781
|View full text |Cite
|
Sign up to set email alerts
|

Patient‐reported extremity symptoms after robot‐assisted laparoscopic cystectomy

Abstract: Aims and objectives To describe patient‐reported extremity symptoms after robot‐assisted laparoscopic cystectomy in patients with bladder cancer. Background Preventive activities for remaining patient safety due to correct positioning play an important part in perioperative nursing care.Extremity injuries are well‐known after prolonged surgery, especially in robot‐assisted urologic surgery in the steep Trendelenburg position. The risk of injury increases due to patient‐related and operative risk factors. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 42 publications
(97 reference statements)
0
2
0
Order By: Relevance
“…Intraoperative brachial plexus injury risk is increased in patients positioned with arms extended, preexisting peripheral neuropathy, a congenital cervical rib, high or low BMI, and a history of smoking or alcohol abuse. 10 Our patient’s BMI and prolonged surgery increased his risk for perioperative neuropathy. The carpal tunnel syndrome treatment performed before his pain medicine referral may have confounded or contributed to the patient’s CRPS.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Intraoperative brachial plexus injury risk is increased in patients positioned with arms extended, preexisting peripheral neuropathy, a congenital cervical rib, high or low BMI, and a history of smoking or alcohol abuse. 10 Our patient’s BMI and prolonged surgery increased his risk for perioperative neuropathy. The carpal tunnel syndrome treatment performed before his pain medicine referral may have confounded or contributed to the patient’s CRPS.…”
Section: Discussionmentioning
confidence: 88%
“…A systematic review of intraoperative peripheral nerve injury with lithotomy for robotic surgery found that preventative measures to stop patients from sliding on operating tables are rarely recorded, thus making it difficult to make recommendations for preventing neuropathy. 10 In our case, documentation simply stated the patient’s arms were tucked with pressure points padded. The American Society of Anesthesiologists taskforce guidelines to prevent perioperative neuropathies discusses reports of brachial and ulnar neuropathies in patients with extremes in body weight, along with a case report of temporary median nerve weakness from elbow overextension.…”
Section: Discussionmentioning
confidence: 89%